Perceived social isolation among health care professional course students using social media in a South Indian metro city - Sucharitha, Sree T.; R. C., Karthik; M., Karthick; S. M., Balaji; Arumugam, Balaji (International Journal Of Community Medicine And Public Health, 2020)
Background: Social isolation has been identified as a state in which individuals lack a sense of belonging, true engagement with immediate family, friends, peers in the form of fulfilling relationships. The subjective form commonly identified as ‘perceived social isolation’(PSI) arises from a feeling of lack of engagement with the above said systems available in one’s living environment and is linked to adverse physical and mental conditions in individuals experiencing it. Aim of the study was to assess perceived social isolation among health care professional course students using social media in a South Indian metro city, Chennai, Tamil Nadu. Methods: A pre-tested questionnaire was designed including socio-demographic features and components to assess social media usage both in duration of time and frequency of usage. Perceived social isolation as assessed by a global validated tool adapted from Patient-Reported Outcomes Measurement Information System (PROMIS) was used in this study. The scores and grades from PROMIS-4 are classified as: low PSI: 4-6, medium PSI: 7-10, high PSI: 11 and above. Data was entered in Microsoft Excel sheet and proportions and tests of significance were performed. Results: In our study we found that PSI was significantly higher among the subjects using social media for than two hours per day. The association between gender, year of studying, time spent on social media on daily basis and PSI scores was found to be statistically significant. (p value >0.05). Conclusions: People with high social media usage perceive being socially isolated than their counterparts with lower use.